THE MOLECULAR GENETIC STUDY OF KRIM-SAGHYZ (Taraxacum hybernum Steven) USING SSR, RAPD AND ISSR MARKERS - B. R. Kuluev; A. V. Fateryga; A. R. Kuluev; E. V. Mikhaylova; A. V. Chemeris (Вавиловский журнал генетики и селекции)
Krim-saghyz (Taraxacum hybernum Steven) is an alternative to Hevea brasiliensis as a source of natural rubber. In Russia, krim-saghyz is common only in the Crimean Peninsula and is traditionally named after it. In spite of its potential for economical use, the genetic structure of the Crimean population of this plant is still unexplored. In this regard, the purpose of our work was a comparative molecular-genetic characterization of T. hybernum from various habitats of the Crimean Peninsula using SSR, RAPD and ISSR markers. According to the plan, we collected achenes, leaves and roots of krim-saghyz in 10 spots all over the Crimean Peninsula. We found the plants in the western part of the southern Crimean coast and the western part of the Crimean foothills, which are two general regions of the area of this species. Total DNA was extracted from dry leaves of krim-saghyz with cetyltrimethylammonium bromide (CTAB). For the first time 12 SSR, 3 RAPD and 3 ISSR markers were tested on krim-saghyz. To observe polymorphism of RAPD- and ISSR-fragments, we used analytical electrophoresis in 1.7 % agarose gel. To compare the length of SSR amplicons, we used gel-electrophoresis in 8 % polyacrylamide gel. We found that the Crimean population of krim-saghyz appears to be genetically homogeneous. This could be due to a small geographic range and apomictic reproduction of this species. However, the phenotypical diversity within the population of T. hybernum is well known from the literature. Consequently, the study of the DNA polymorphism of this species should be continued, in particular, with the help of high-resolution techniques.